Factors Determining Female Labor Participation in Job Market in the Middle East and North Africa (MENA) Countries - Almiman Anas Abdulrahman; Pradikta Aris Chandra; Altamimi Raeef (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2020)
Women’s engagement in the broader social life is part of policy objectives in today’s world that most governments aim to achieve. Likewise, the issue is crucial in most Muslim majority countries, especially in the Middle East and North Africa (MENA). As the regions have characteristics of a smaller number of women’s participation in the formal labor market than many other countries, this study investigated the factors that determine women’s participation by measuring data of governance, industrial transformations, and education from 1980 to 2014. This study used robust panel data methods to calculate the interdependencies of those variables. Based on the estimation, prominent factors that have positive correlations with the participation are good governance and the transitions from agriculture to industrial and service economy. Meanwhile, financial literacy and education have limited impacts on participation.